Multiple-Factor Analyses of Futile Recanalization in Acute Ischemic Stroke Patients Treated With Mechanical Thrombectomy - Pan, Hui; Lin, Changchun; Chen, Lina; Qiao, Yuan; Huang, Peisheng; Liu, Bin; Zhu, Yueqi; Su, Jingjing; Liu, Jianren (Frontiers in Neurology, 2021)
BACKGROUND AND PURPOSE: Acute ischemic stroke (AIS) is a serious threat to the life and health of middle-aged and elderly people in China. Mechanical thrombectomy offers the advantages of rapid recanalization, but the response of patients to this treatment varies greatly. This study investigated the risk factors for futile recanalization in Chinese AIS patients after thrombectomy through multivariate analyses. METHODS: A retrospective study was conducted in AIS patients who underwent thrombectomy and reperfusion. Using the modified Rankin Scale (mRS) at 90 days after the operation, the patients were divided into two groups, the meaningful recanalization group (mRS ≤ 2), and the futile recanalization group (mRS > 2). Multivariate logistic regression analyses were performed, and the receiver operating characteristic (ROC) curve was used to construct a risk prediction model for futile recanalization. RESULTS: A total of 140 patients were enrolled, 46 patients in the meaningful recanalization group and 94 patients in the futile recanalization group. The two groups were significantly different in age, preoperative National Institute of Health Stroke Scale (NIHSS) score, and collateral circulation ASITN/SIR grade (P < 0.05). In multivariate regression analyses, patients’ age ≥ 71, NIHSS ≥ 12, and ASITN/SIR ≤ 3 were risk factors for futile recanalization. Hence, an ANA score scale consisting of age, NIHSS score, and ASITN/SIR grade factors can effectively predict the risk for futile recanalization (area under curve 0.75, 95% CI 0.67–0.83, specificity 67.4%, and sensitivity 73.4%). The proportion of patients with futile recanalization in ANA groups 0, 1, 2, and 3 were 21.05%, 56.76%, 79.03% and 90.91%, respectively. CONCLUSIONS: Old age, high baseline NIHSS, and poor collateral circulation are risk factors for futile recanalization in Chinese AIS patients treated with thrombectomy. An ANA score that considers age, NIHSS, and collateral ASITN/SIR can effectively predict the risk for futile recanalization.